Management Model under the BPM Approach and DT Tools to Increase the Level of Sales in a Peruvian Nanostore - Quiroz-Flores, Juan Carlos (2022)
Retail trade is one of the main economic activities most develop d in the MYPES of Peru; this sector faces the rapid growth of its competitors, which are convenience stores and discount stores, due to the model of modern business that they handle, affect the nanostores. According to the above, nanostores must acquire new ways to grow and outperform their competitors. Therefore, they must adapt to recent technological advances and apply more appropriate strategies for their growth. This study aims to redesign the commercial process of these businesses through the BPM methodology and DT tools to generate higher sales since they are currently at 40. 36% caused by poor management in their business process. After applying the model through the implementation method, sales increased by 69.55%, thus generating a more significant profit.